Sodium-glucose co-transporter 2 inhibitors use and the risks of genital and urinary tract infection: What should we know? - Du-An Wu; Bang-Gee Hsu; Yu-Li Lin (Tzu Chi Medical Journal, 2025)
Sodium-glucose co-transporter 2 (SGLT2) inhibitors have convincingly demonstrated efficacy in reducing cardiovascular (CV) and renal complications in patients with diabetes mellitus, chronic kidney disease, and heart failure. However, their use is also linked to the concern of some adverse events, the most common being genital and urinary tract infections (UTIs). This review summarizes the risks of genital and UTIs of SGLT2 inhibitors across large-scale clinical trials, meta-analyses, and real-world cohort studies. SGLT2 inhibitors are shown to significantly increase the risk of genital infections in clinical trials and real-world observational studies and marginally increase the risk of UTI in meta-analyses. We also discuss the potential pathogenesis of SGLT2 inhibitor-related infections and identify the susceptible risk factors. Since most genital and UTIs associated with SGLT2 inhibitors are mild and treatable and severe infections are rare, the use of SGLT2 inhibitors is highly recommended in patients who meet the inclusion criteria of clinical trials, where the CV and renal benefits outweigh the infection risks. For all users of SGLT2 inhibitors, preventive strategies, patient education, and careful monitoring are essential to minimize the infection risks. Furthermore, we address an unmet need regarding SGLT2 inhibitors among vulnerable populations, such as older adults, frail, and immunocompromised patients, underscoring the importance of observational studies from the real-world data. Future research should focus on identifying the high-risk groups, developing SGLT2 inhibitors with a lower infection profile and establishing effective prevention strategies to mitigate the risk of genital and UTIs associated with these medications.